Epidemiological profile of orthopedics and traumatology patients in Palmas, Tocantins, Brazil - Ediana Vasconcelos da Silva; Kércio Jeaneryson Nogueira de Sousa Leite; Roqueline Ametila e Gloria Martins de Freitas Aversi-Ferreira; Tales Alexandre Aversi-Ferreira (Acta Scientiarum. Health Sciences, 2021)
Epidemiological studies, both in general and specifically, are part of the health promotion process and prophylactic actions that can generate treatment plans for a population, however, the accomplishment of prophylactic work in relation to musculoskeletal (i.e., traumatological) problems must start from the specific and go to the general, from cities to a national plan, since each population has its own characteristics in the general picture of conditions. Hypothetically, the epidemiological profile in traumatology and orthopedics, due to the general behavior in the national territory, presents the lack of prevention; in this way, is necessary to verify. This work aims to determine the incidence of orthopedic and traumatological problems in the region of Palmas, state of Tocantins (TO), Brazil, in order to contribute to a possible prophylactic plan for the population of the region. The data of the present study agree with most other studies about the orthopedic profile in terms of gender, age and problems with vertebral column, in general. However, the finding that most of the conditions were associated with scoliosis was unexpected, as it differs from the findings of most studies. It was possible to establish a profile of patients seen at the clinic-school and indicate the management of training for health professionals related to the treatment of people over the age of 40 years. The importance of the action of physiotherapists in the processes of prevention and primary care was evident given the patients indicated in this and other articles who need help with traumatic diseases.